Biodegradation of vapor-phase toluene in unsaturated porous media: Column experiments. (April 2016) - Khan, Ali M.; Wick, Lukas Y.; Harms, Hauke; Thullner, Martin
Abstract: Biodegradation of organic chemicals in the vapor phase of soils and vertical flow filters has gained attention as promising approach to clean up volatile organic compounds (VOC). The drivers of VOC biodegradation in unsaturated systems however still remain poorly understood. Here, we analyzed the processes controlling aerobic VOC biodegradation in a laboratory setup mimicking the unsaturated zone above a shallow aquifer. The setup allowed for diffusive vapor-phase transport and biodegradation of three VOC: non-deuterated and deuterated toluene as two compounds of highly differing biodegradability but (nearly) identical physical and chemical properties, and MTBE as (at the applied experimental conditions) non-biodegradable tracer and internal control. Our results showed for toluene an effective microbial degradation within centimeter VOC transport distances despite high gas-phase diffusivity. Degradation rates were controlled by the reactivity of the compounds while oxic conditions were found everywhere in the system. This confirms hypotheses that vadose zone biodegradation rates can be extremely high and are able to prevent the outgassing of VOC to the atmosphere within a centimeter range if compound properties and site conditions allow for sufficiently high degradation rates. Graphical abstract: Highlights: The column setup allows resolving vapor-phase VOC concentration gradients at cm scale resolution. Vapor-phase and liquid-phase concentrations are measured simultaneously. Isotopically labelled VOC was used as reference species of low biodegradability. Biodegradation rates in the unsaturated zone can be very high and act at a cm scale. Unsaturated material can be an effective bio-barrier avoiding biodegradable VOC emissions. Abstract : Microbial degradation activity can be sufficient to remove VOC from unsaturated porous media after a few centimeter of vapor-phase diffusive transport and mayeffectively avoid atmospheric emissions.